2020
DOI: 10.1002/mus.27026
|View full text |Cite
|
Sign up to set email alerts
|

Identifying putative cerebrospinal fluid biomarkers of amyotrophic lateral sclerosis in a north Indian population

Abstract: Introduction: Evidence-based information about cerebrospinal fluid (CSF) levels of biomarkers in patients with amyotrophic lateral sclerosis (ALS) is limited. Methods: Vascular endothelial growth factor (VEGF) and its receptor vascular endothelial growth factor receptor 2 (VEGFR2), optineurin (OPTN), monocyte chemoattractant protein-1 (MCP-1), angiogenin (ANG), and TAR DNA-binding protein (TDP-43) were quantified by enzyme-linked immunoassay in the CSF of 54 patients with sporadic ALS and 32 controls in a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Subsequent studies have further confirmed the downregulation of VEGF in the spinal cord of SOD mice [ 16 , 19 ]. Consistent with this observation, reports indicate a reduction in VEGF levels in both the spinal cord and cerebrospinal fluid (CSF) of ALS patients [ [20] , [21] , [22] ].…”
Section: Introductionsupporting
confidence: 61%
“…Subsequent studies have further confirmed the downregulation of VEGF in the spinal cord of SOD mice [ 16 , 19 ]. Consistent with this observation, reports indicate a reduction in VEGF levels in both the spinal cord and cerebrospinal fluid (CSF) of ALS patients [ [20] , [21] , [22] ].…”
Section: Introductionsupporting
confidence: 61%
“…The full text of 10 studies was further evaluated. Finally, a total of seven studies were included in the meta-analysis [25][26][27][28][29][30][31].…”
Section: Study Selectionmentioning
confidence: 99%
“…However, increased VEGF-A expression exhibits a neuroprotective effect on hypoxic motor neurons, hampering ALS-like motor neuron degeneration, and vice versa. 34 Additionally, VEGF-A promotes vascular smooth muscle cell proliferation and migration. 35 VEGF-A is also implicated in hematopoiesis, such as blood vessel formation and survival of hematopoietic stem cells (HSCs).…”
Section: Molecular and Functional Characterization Of Vegfmentioning
confidence: 99%
“…The pathogenesis of amyotrophic lateral sclerosis (ALS) is associated with VEGF‐A expression. However, increased VEGF‐A expression exhibits a neuroprotective effect on hypoxic motor neurons, hampering ALS‐like motor neuron degeneration, and vice versa 34 . Additionally, VEGF‐A promotes vascular smooth muscle cell proliferation and migration 35 .…”
Section: Molecular and Functional Characterization Of Vegfmentioning
confidence: 99%